An Innovation of Music Art Learning Media in the Covid-19 Pandemic to Develop Student Character - Saputra, Oktafian Harys; Utomo, Udi; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2020)
The COVID-19 pandemic has resulted in learning activities that took place face-to-face, turning into distance learning. Teachers need to adjust to this condition by making innovations to provide good educational services to students. This study aims to describe and analyze an innovation of media use in music art learning in the Covid 19 pandemic to develop the character of students at SMP Nasima Semarang. The research method used is qualitative research with a case study design. The data collection process was carried out by observation, interviews, and literature study. The data analysis was carried out by using three activity lines according to Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results of this study is the use of learning videos uploaded to social media namely Youtube as a form of innovation in distance learning activities at SMP Nasima Semarang, which previously used powerpoint media in face-to-face learning in class. The use of video in distance learning makes it easy for teachers in delivering material, even though the manufacturing process requires more effort. There are character values instilled in students through the use of instructional videos, namely responsibility, curiosity, and honesty. The benefit of this study is as an overview of learning media innovation that can be used as a reference in implementing learning in the COVID-19 pandemic.